Jejak Jalur Rempah Nusantara dalam Catatan Sejarah Qatar: Al-Hajri, Ali Bin Ghanem. Qaṭar fī ‘Uyūn al-Rahhālah, First edition. Doha, Qatar: Hamad bin Khalifa University Press, 2020. 167 pp. ISBN: 978-9927141294. - Karyadi, Fathurrochman (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2025)
This research discusses Qatar's role in the Nusantara spice trade route using the book "Qaṭar fī ‘Uyūn al-Rahhālah" by Ali Bin Ghanem Al-Hajri as the primary source. According to Al-Hajri, Qatar serves as a crucial transit center in the spice trade, receiving ships from the Far East and distributing their goods to various regions. Although Qatar does not produce these spices, the country plays a vital role in the trading network. This study also compares the maritime trade routes described by Al-Hajri with the records of Ibn Majid, while highlighting the role of Arab traders in the history of spice trade. By considering these historical records, this research provides valuable insights into Qatar's relationship with spice trade and the Southeast Asian region, particularly the Nusantara.